2021
DOI: 10.1177/00144029211007150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using Virtual Manipulatives for Students With Disabilities: Three-Level Multilevel Modeling for Single-Case Data

Abstract: We synthesized studies published since 2000 that assessed the effects of using virtual manipulatives to increase the mathematical accuracy of students with disabilities. We extracted a total of 1,796 raw data points from 114 cases across 35 single-case studies. By applying three-level multilevel modeling, we analyzed both immediate effects and trends during the intervention phase as well as moderation effects related to student characteristics (case level) and intervention features (study level). Both the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…If the given task requires skills beyond the student's independent or instructional skill level, a teacher should consider interventions that build preliminary academic skills that provide or scaffold support to the student before or during the assigned task. One example is to use instructional aids such a number line, manipulatives, graduated guidance, or multiple exemplars during the task to aid the student in responding (Shin et al, 2021). Another example is using student-directed interventions like Cover, Copy, and Compare or Performance Feedback to build perquisite skills to promote learning and increase performance (Joseph et al, 2012;Stocker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…If the given task requires skills beyond the student's independent or instructional skill level, a teacher should consider interventions that build preliminary academic skills that provide or scaffold support to the student before or during the assigned task. One example is to use instructional aids such a number line, manipulatives, graduated guidance, or multiple exemplars during the task to aid the student in responding (Shin et al, 2021). Another example is using student-directed interventions like Cover, Copy, and Compare or Performance Feedback to build perquisite skills to promote learning and increase performance (Joseph et al, 2012;Stocker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mathematics instruction using virtual manipulatives can be implemented in three ways: (a) teacher-led instruction, (b) teacher-guided instruction, and (c) technology-assisted instruction (Bouck et al, 2021; Park, Bryant, & Shin, 2021; Shin et al, 2021). These instructional methods are effective for teaching mathematics to a wide range of grade levels.…”
Section: Use Of Virtual Manipulativesmentioning
confidence: 99%
“…Virtual manipulatives can be included in various technology environments, such as single representation (i.e., interactive image only), multiple representation (i.e., interactive visual models accompanied with numerical or text information), tutorials, gaming , and simulation (Moyer-Packenham & Bolyard, 2016), encouraging students to engage in learning. Studies have revealed that students with disabilities who received mathematics interventions using virtual manipulatives showed both immediate effects and growth over time in various concepts and subjects within mathematics (Bouck et al, 2021; Park, Bryant, & Shin, 2021; Shin et al, 2021).…”
mentioning
confidence: 99%
“…VM have been defined as “an interactive, Web-based visual representation of a dynamic object that presents opportunities for constructing mathematical knowledge” (Moyer et al, 2002 , p. 373). VM were initially developed as Flash or Java programs, but now are predominantly HTML5 or app based (Shin et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%